2015
DOI: 10.1371/journal.pone.0138265
|View full text |Cite
|
Sign up to set email alerts
|

Differential Role of the T6SS in Acinetobacter baumannii Virulence

Abstract: Gram-negative bacteria, such as Acinetobacter baumannii, are an increasing burden in hospitals worldwide with an alarming spread of multi-drug resistant (MDR) strains. Herein, we compared a type strain (ATCC17978), a non-clinical isolate (DSM30011) and MDR strains of A. baumannii implicated in hospital outbreaks (Ab242, Ab244 and Ab825), revealing distinct patterns of type VI secretion system (T6SS) functionality. The T6SS genomic locus is present and was actively transcribed in all of the above strains. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
115
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(121 citation statements)
references
References 40 publications
(66 reference statements)
3
115
0
Order By: Relevance
“…The T6SS is a class of macromolecular secretion machines that could be regarded as a potent weapon used by many Gramnegative bacteria to kill competitors (20). It has been shown that certain strains of A. baumannii produce a functional T6SS, which has been found to be implicated in virulence and host colonization in a strain-specific manner (21)(22)(23)(24).…”
Section: Novel Traits Modulated By Light In a Baumanniimentioning
confidence: 99%
“…The T6SS is a class of macromolecular secretion machines that could be regarded as a potent weapon used by many Gramnegative bacteria to kill competitors (20). It has been shown that certain strains of A. baumannii produce a functional T6SS, which has been found to be implicated in virulence and host colonization in a strain-specific manner (21)(22)(23)(24).…”
Section: Novel Traits Modulated By Light In a Baumanniimentioning
confidence: 99%
“…Notably, the main T6SS cluster does not contain vgrG genes, which are instead scattered throughout the genome. The VgrG proteins of Acinetobacter, which differ in number from strain to strain, do not seem to include effector domains (86,88). Instead, bioinformatic analyses suggest that the proteins are most likely to mediate the secretion of adjacently encoded toxic effectors, with cognate immunity proteins being encoded nearby (88).…”
Section: Protein Secretionmentioning
confidence: 99%
“…The primary function of the T6SS in Acinetobacter seems to be to kill competing bacteria, and Acinetobacter spp. with active T6SSs are able to kill a wide variety of other bacteria, including other strains of the same species (64,(87)(88)(89).…”
Section: Protein Secretionmentioning
confidence: 99%
See 2 more Smart Citations